Prevalence of musculoskeletal disorders in delivery personnel - Srinivasan, Revathi; Reza, Ahsan; Krishna Kumar, A. K. Vijay (International Journal Of Community Medicine And Public Health, 2023)
Background: Musculoskeletal problems are widespread in the elderly, but they are also becoming more common in the younger population as a result of changes in lifestyle and employment. In this study we will be assessing the musculoskeletal disorders in delivery personnel. Methods: 200 delivery personnel took part in an offline survey at several e-commerce companies’ delivery hubs as part of this observational study, based on inclusion and exclusion criteria. In addition to questions from the Nordic Questionnaire, the form included basic demographic information. Results: The current study showed that the musculoskeletal pain in the last 12 months showed the prevalence was higher for lower back 60(30%) followed by 18(9%) for neck. The seven days prevalence showed 43(21.5%) for lower back followed by 11(5.5%) for neck. Prevention to do the work due to the pain in last 12 months showed highest percentage of the respondents experienced it due to lower back pain. The statistics further showed majority of people who had musculoskeletal pain from last 12 months were working for more than 8 hours per day (52.3%). Conclusions: We can conclude that MSDs are common in all three groups, namely pain in the past year, pain in the past week, and activity prevention. This incidence demonstrates that MSDs can impact delivery personnel even at younger ages, which can be avoided by reducing workload and observing adequate safety procedures while working.